Socio-Economic Conditions of Fishermen: Evidence from Hakaluki Haor of Bangladesh - Khanum, Romaza (Asian Business Review, 2013)
The study explores the socio-economic conditions of fishermen in Hakaluki haor of Moulvibazar district. The main information was used in this regard to measure the poverty incidence such as family size, annual income, expenditure of food and non-food items, education level, etc. The study also estimates the poverty level by using CBN method. About 42 and 68% haor fishermen were below the lower and upper poverty lines respectively. The study suggests that the Government should take haor based policy to reduce poverty level of fishermen.